ENERGY EVALUATION OF ENSURING THE SAFETY OF BUILDINGS AND STRUCTURES FROM SEISMIC AND FIRE IMPACTS - Abdullaev Ibrohim; Yunusaliyev Elmurod (Journals Park Publishing, 2024)
The necessity of ensuring the safety of buildings and structures has made it possible to obtain interesting results by simplifying the surface approach. It was determined that for the self-evolution of the system, the probability of transition from a less probable state to a more probable state in the case of a more ordered arrangement of its molecules is higher. It was shown that if the environment has the necessary conditions for this, the probability of such a transition increases further.
Keywords: Proteology, fire seismology, pyrolysis, wollastonite, entropy, nanosurface.